Exploratory spatial analysis of topographic surface metrics for the prediction of water table occurrence - Sousa, F. Raquel R.F. de (2014)
Starting from the premise that water table in aquifers follows topographic surface as well as underground flow direction tends to be consistent with the surface streams flow directions, the present work presents the essays of the research to define a model that predicts, through a piecewise multiple regression, groundwater level in the Estremoz-Cano Aquifer System and in the surrounding igneous and metamorphic rocks of the OMZ as a function of topography, namely a set of terrain metrics like curvature and structural curvature to be related with the static water level (SWL) measured on dug wells of farms and cottages. The spatial analysis of the topographic surface draining water to the sampled aquifer systems is based on a DEM at different resolutions to acquire and infer information about the surface shape and processes, namely the hydrologic characteristics of the basins and its relation with infiltration process and the prediction of water table; Análise exploratória da métrica da superfície topográfica para previsão do nível freático da água subterrânea ### Resumo: O presente trabalho parte da premissa de que não só o nível freático acompanha a linha topográfica do terreno, mas também a direcção de escorrência das bacias subterrâneas tende a coincidir com a direcção predominante de escorrência das bacias hidrográficas à superfície, principalmente em aquíferos fraturados. O presente trabalho apresenta o estudo realizado na investigação de um modelo que explique o nível freático no sistema aquífero Estremoz-Cano e na área circundante a este, nas rochas ígneas e metamórficas da ZOM, em função da curvatura e das características métricas do terreno. Na base dos modelos desenvolvidos estiveram os dados de elevação do terreno a diferentes resoluções, a curvatura e a convexidade deste, assim como as características hidrológicas e a influência destas nos processos de infiltração.